Integrin Alpha E (CD103) Limits Virus-Induced IFN-I Production in Conventional Dendritic Cells - Duhan, Vikas; Khairnar, Vishal; Kitanovski, Simo; Hamdan, Thamer A.; Klein, Andrés D.; Lang, Judith; Ali, Murtaza; Adomati, Tom; Bhat, Hilal; Friedrich, Sarah-Kim; Li, Fanghui; Krebs, Philippe; et al. (Frontiers in Immunology, 2021)
Early and strong production of IFN-I by dendritic cells is important to control vesicular stomatitis virus (VSV), however mechanisms which explain this cell-type specific innate immune activation remain to be defined. Here, using a genome wide association study (GWAS), we identified Integrin alpha-E (Itgae, CD103) as a new regulator of antiviral IFN-I production in a mouse model of vesicular stomatitis virus (VSV) infection. CD103 was specifically expressed by splenic conventional dendritic cells (cDCs) and limited IFN-I production in these cells during VSV infection. Mechanistically, CD103 suppressed AKT phosphorylation and mTOR activation in DCs. Deficiency in CD103 accelerated early IFN-I in cDCs and prevented death in VSV infected animals. In conclusion, CD103 participates in regulation of cDC specific IFN-I induction and thereby influences immune activation after VSV infection.